Perspective of personalized treatment of immunoglobulin A-nephropathy - Komissarov, K.S. (KIDNEYS, 2021)
The search of personalized treatment for a subject with immunoglobulin A-nephropathy (IgAN) attracts attention of nephrologists all over the world. According to the Kidney Disease: Improving Global Outcomes guidelines, persistentproteinuria > 1 g/day for 3–6 months despite optimized supportive care is considered as indication to corticosteroid/immunosuppressive treatment in IgAN patients. The Oxford classification study and subsequent investigations have revealed the value of pathologic risk factors in disease progression regardless of proteinuria, blood pressure level and glomerular filtration rate at renal biopsy. Meanwhile, new studies have provided an improved understanding of the pathogenetic mechanisms leading to kidney tissue damage in IgAN. This review provides the possibility of using treatment based on pathological changes in the individual patient with IgAN, taking into consideration the pathogenetic mechanisms prevailing at the time of renal biopsy.